The impact of major trauma centre designation on routine orthopaedic trauma care. (July 2022) - Archer, James; Odeh, Abdulrahman; Piper, Danielle; Moore, Ellen; Butt, Annisa; Fawdington, Ross; Fenton, Paul
Introduction: Major Trauma networks were introduced in 2012 to improve care for patients with major traumatic injuries. Current evidence suggests that this has been successfully achieved, however, there are implications for 'routine trauma care' of patients who attend a major trauma centre. Methods: We assessed time from injury to surgery in August to October in 2011 and 2019. We also assessed the National Hip Fracture Database outcomes for time to surgery for hip fracture patients. Results: Average wait times for ankle surgery increased from 4.9 days (18 patients) in 2011 to 7.0 in days (26 patients) in 2019, whilst for distal radius fracture surgery increased from 3.9 days (36 patients) to 6.5 days (23 patients); the percentage of patients who received their hip fracture surgery within the recommended 36 hours was 53.7% in 2011 (322 patients) compared to 66.7% in 2019 (375 patients). Conclusion: The wait times for 'routine trauma care' have increased since the introduction of the major trauma network. This is probably due to the large demand on major trauma centres presented by complex trauma patients. However, the number of patients undergoing hip fracture surgery within 36 hours has improved, probably driven by the NHS tariff for hip fracture care. Changes to the current major trauma system or an increase in resources are required to help reverse this trend.